Family Perception and Adaptation in Caring for Members with Schizophrenic Mental Disorders: An Ethnographic Study in Surabaya Rural Communities - Sumiyati, Sumiyati (Fakultas Ilmu Kesehatan Universitas Gresik, 2024)
Schizophrenia is a severe mental disorder that creates a significant burden on families, especially in rural communities with limited access to services. Previous research has focused on family burdens and stigma, but few have explored in depth cultural perceptions and family adaptation strategies in rural Indonesia. This study aims to identify family perceptions of schizophrenia, explore the adapted strategies developed, and analyze the interaction between perception, stigma, and family dynamics in shaping treatment patterns in rural communities in Surabaya. The research uses an ethnographic qualitative design. Sampling was carried out purposively and snowball, involving 18 families as participants. Data were collected through in-depth interviews, participant observations, and document studies. Data analysis uses thematic analysis. The findings of the study revealed that family perceptions are dominated by cultural beliefs (guna-guna, santet) and religious beliefs (God's test). Social stigma drives social strategies of concealment and withdrawal. Behind these challenges, families demonstrate resilience through complex adaptation strategies, including emotional (acceptance), practical (role sharing, integrative treatment), and spiritual (worship, resignation) dimensions. The study concluded that families in rural communities develop unique and layered adaptation mechanisms, where culture acts as a source of resistance as well as a source of resilience. The implications of the findings emphasize the need to develop culturally sensitive and local strengths-based mental health interventions, as well as policies that support strengthening the role of families as primary caregivers.